Socialization and training on the use of digital media and digital applications for teracher personality branding in the challenges of Generation Z Era Society 5.0 in Tembung Village, Deli Regency Serdang Province of North Sumatra. - Noer Fadlan, Muhammad; Landong, Ahmad; Shabrina Anshor, Arrini; Dahnial, Irfan (Journal of Community Service For Indonesian Society, 2023)
This research aims to provide training on the use of digital media and digital applications in developing teacher personality branding in the challenges of generation Z. Generation Z, as a generation that grows up in the digital era, has different preferences and needs in terms of learning and interactions with teachers. This study uses a qualitative approach involving participants consisting of teachers who have attended training on the use of digital media and digital applications. Data was collected through in-depth interviews and participatory observation. The results showed that this training had a positive impact on developing effective teracher personality branding for generation Z. Teachers who participated in the training experienced increased knowledge and skills in using digital media and digital applications relevant to the needs of generation Z. They were able to create interesting and relevant content, build strong relationships with students, and utilize social media platforms to expand the reach and influence of teachers. In addition, this training also increases teachers' understanding of the characteristics of Generation Z, including their preferences in learning, communication styles, and use of technology. Trained teachers can harness the power of digital media and digital applications to create more interactive, collaborative and relevant learning experiences for generation Z.